Comparison Study of AN Removal in Different Geometrical Shape of a Pilot-scale Aerated EAFS Filter Systems - Wan Mohamed, Wan Afnizan (International Journal of Integrated Engineering, 2019)
Two types of aerated electric arc furnace slag filter systems in dissimilar geometry shape; the vertical upward-flow and horizontal-flow were studied in treating domestic wastewater in a tropical climate country. These filters were operated at the same hydraulic loading rate (HLR) set-up of 2.72 m3/m3.day and the removal efficiency of the contaminant was studied and analyzed. Air was supplied to both systems at 10 L/min and the observation of dissolved oxygen concentration on ammonium nitrogen (AN) removal were finally compared. The results revealed that both systems were efficiently able to produce ammonium nitrogen (AN) removal of more than 85%; however with regard to individual’s system performance, the vertical upward-flow electric arc furnace slag filter (VFEAFS) system was found excellent than the horizontal-flow electric arc furnace slag filter (HFEAFS) system. The mean value of AN effluent concentration equally by the systems were discovered easily to follow regulated standard A of Malaysian sewage discharge limit (10 mg NH4-N/L). The results obtained in this pilot-scale study indicated that the geometry shape of filter system has the effect on the removal of ammonium nitrogen, particularly in the aerated VFEAFS system due to their capability to produce higher and uniform oxygen distribution in the whole filter system, and eventually resulted in a lower AN effluent concentration rather the one operated in the horizontal-flow direction. Based on these findings, it is also recommended that further study on the aerated rock filter should be evaluated for the other parameters (total kjedahl nitrogen (TKN), nitrate-nitrogen (NO3-N), pH, and alkalinity) which on the other hand are believed possess the potential to accommodate nitrification process in the system and eventually eliminate nitrogen pollutant from domestic wastewater.